Secured and trusted three-tier grid architecture. (7th May 2010) - Varalakshmi, P.; ThamaraiSelvi, S.
Grid aims at utilising resources efficiently through coordinated resource sharing and problem solving in a virtual organisation spanning geographical boundaries. A three-tier grid architecture consisting of Service Providers or Resource Provider (SP/RP), brokers and Regional Resource Administrators (RRA), is secured using DDoS attack defense mechanism and spam filtering mechanisms that endeavour to optimise the resource utilisation. An overlay network of Anomaly Detection Agents (ADA) is set up at the RRA level which enables deployment of collaborative defense mechanisms. The presence of these mechanisms minimises the wastage of resources which can be put to effective use in grid applications.